Association between serum gamma-glutamyl transferase and serum uric acid levels in Chinese females: A cross-sectional study. (2nd October 2017) - Ya, Zhao; Fei, Liu; Yue, Zeng; Dan, Liu; Neng-bo, Lin; Yi, Luo; Ying, Miao; Qin, Wan
ABSTRACT: Objective : To investigate the association between serum gamma-glutamyl transferase (GGT) levels and serum uric acid levels in middle-aged and elderly Chinese females.Methods : A cross-sectional population survey was performed in Luzhou, China (2014). Questionnaires, physical examinations and biochemical tests were conducted. Finally, we included 2486 females who were > 40 years old as participants. Multiple linear regression analysis was used to estimate the association of serum acid levels and other variables. Serum GGT levels were divided into four groups using the 25th, 50th and 75th percentiles as cut-off points. Finally, binary logistic regression analysis was used to investigate the association of different serum GGT quartiles with the risk of hyperuricemia.Results : The prevalence of hyperuricemia was 25.1% in the studied population and gradually increased across the serum GGT quartiles ( P < 0.05). Binary logistic regression analysis showed that compared with subjects in the lowest quartile of serum GGT levels, the adjusted odds ratio (ORs) for uric acid in the highest quartile was 2.34 (95% confidence interval (CI), 1.68–3.28, P < 0.001), after corrections for TG, TC, HDL-C, LDL-C, creatinine (CR), GGT, AST, ALT, fasting plasma glucose (FPG), postprandial 2-h plasma glucose, hemoglobin A1c(HbA1c), age, BMI, SBP, DBP, waist-to-hip ratio and neck circumference (NC).Conclusions : The serum GGT level is associated with hyperuricemia in middle-aged and elderly Chinese females.